Modified Polymeric Biosorbents from Rumex acetosella for the Removal of Heavy Metals in Wastewater - Ligarda Samanez, Carlos A. (2022)
The contamination of water resources by effluents from various industries often contains heavy metals, which cause irreversible damage to the environment and health. The objective was to evaluate different biosorbents from the weed Rumex acetosella to remove metal cations in wastewater. Drying, grinding and sieving of the stems was carried out to obtain the biomass, re taining the fractions of 250 to 500 µm and 500 to 750 µm, which served to obtain the biosorbents in natura (unmodified), acidic, alkaline, and mixed. Proximal analysis, PZC, TOC, removal capacity, influence of pH, functional groups, thermal analysis, structural characteristics, adsorption iso therms, and kinetic study were evaluated. The 250 µm mixed treatment was the one that presented the highest removal percentages, mainly due to the OH, NH, -C-H, COOH, and C-O functional groups achieving the removal of up to 96.14% of lead, 36.30% of zinc, 34.10% of cadmium and 32.50% of arsenic. For contact times of 120 min and an optimum pH of 5.0, a loss of cellulose mass of 59% at 328 °C and a change in the surface of the material were also observed, which allowed for obtaining a topography with greater chelating capacity, and the Langmuir and pseudo-second or der models were better fitted to the adsorption data. The new biosorbents could be used in wastewater treatment economically and efficiently.